A Rare Case of High Physical Endurance in Transfusion-Dependent Thalassemia Patients with Poor Cardiac Functions - Nathasha Brigitta Selene; Ayudra Fitrananda; Natasha Yemima Situmorang; Kamilia Rifani Ufairah; Stephen Diah Iskandar; Pustika Amalia Wahidiyat (Thalassemia Reports)
Background/Objectives: Chronic anemia and iron overload in thalassemia lead to organ failures, including the heart, liver, endocrine glands, and spleen. Comprehensive multidisciplinary management is pivotal in improving patients’ clinical outcomes and well-being. The report aims to present a rare case of improved clinical condition in a transfusion-dependent thalassemia patient. Methods: Medical summaries were collected to compare patients’ conditions at various time frames. Furthermore, the report was composed in chronological order. Results: A 31-year-old male diagnosed with beta-thalassemia major and multiple comorbidities, including diabetes with a history of diabetic ketoacidosis, heart failure with a history of cardiac arrest, hepatomegaly, severe thoracolumbar scoliosis, and depression, exhibited a high physical endurance. The patient managed to maintain a strong treatment adherence and undergo intensive regular multidisciplinary follow-ups. The patient gained cardiac function improvement and metabolic stabilization, leading to completing a 5 k marathon without complication. Conclusions: Intensive management of iron overload through double oral chelation allows organ function improvement. Better mental health attenuates the patient’s overall well-being and is attributed to the ability to gain high physical endurance.